Lighting conditions at an operating room in a Portuguese maternity - Monteiro, Ana (2012)
Lighting is one of the most important factors in human interaction with the environment. Poor lighting may increase the risk of accidents and could also cause a variety of symptoms including: rapid fatigue, headaches, eyestrain, tired eyes, dry eyes, ocular surface symptoms (watery and irritated eyes), decreased concentration and stress. Specific disorders: degeneration of the sharpness of vision (blurred and double vision) and slowness in changing focus. Apart from the advantages in the health and welfare for the workers, good lighting also leads to better job performance (faster), less errors, better safety, fewer accidents and less absenteeism. The overall effect is: better productivity. Good lighting includes quantity and quality requirements, and should necessarily be appropriate to the activity/task being carried out, bearing in mind the comfort and visual efficiency of the worker.